ANALISA KERUSAKAN MESIN CNC VERTICAL TURNING LATHE DENGAN MENGGUNAKAN METODE FAILURE MODE AND EFFECT ANALYSIS - Gustina Gustina; Dina Satriani; Vina Vijaya Kusuma (Teknik Informatika Fakultas Ilmu Komputer, 2020)
PT X is a manufacturing company that produces high-precision components, using 13 units of CNC machines as production tools. The target of achieving technical availability for each machine unit is at least 85% in one year. One of the machine units, namely the CNC vertical turning lathe machine in this company, was only able to reach 64% of the technical availability value due to the impact of the damage. This study aims to determine the causes of component failure in machine units that have low technical availability, namely the CNC vertical turning lathe, using the Failure Mode and Effect Analysis method. The results showed that during one year, the CNC vertical turning lathe was damaged 19 times, on 7 different machine components. With the results of data processing using the Failure Mode and Effect Analysis method, it is known that of the 7 components that were damaged, the component that had the highest risk priority number value was the electronic component with an RPN value of 405.